Commitment Readiness and Relationship Formation. (August 2018) - Hadden, Benjamin W.; Agnew, Christopher R.; Tan, Kenneth
The concept of being ready for a relationship is pervasive in popular culture, but theoretical and empirical research on readiness is lacking. We offer a conceptualization of commitment readiness and provide some of the first empirical work examining readiness among single individuals—specifically how this construct shapes various aspects of relationship formation. Using data from five independent samples of individuals not involved in romantic relationships, we first establish that commitment readiness is associated with more interest in developing a close romantic relationship (Studies 1a, 1b, 2) and with active pursuit of relationship initiation (Study 2). We then test whether readiness among single individuals longitudinally predicts both the likelihood of later entering a relationship and, ultimately, how committed individuals are to a future relationship (Studies 3a, 3b, 3c). Implications of commitment readiness specifically, and perceived personal timing more generally, for the social psychology of relationships are discussed.